Mesmerism in Late Victorian Theatre - García Walsh, Katerina (Complutense Journal of English Studies, 2020)
Originating as a medical practice and ultimately rejected as pseudoscience, mesmerism evolved into a literary symbol in the later Victorian era. This paper focuses on three plays that use mesmerism as a symbol of marital control and domination: the comedy His Little Dodge (1896), adapted from Le Systême Ribardier (1892), by George LeFeydeau and Maurice Hennequin; Trilby (1895), adapted from the novel by George Du Maurier; and, finally, Johan Strindberg’s The Father (1893). The mesmeric power one character imposes over another, overriding both consent and awareness in the trance state, serves both to reaffirm hierarchies of power and highlight anxieties about social change in the fin-de-siècle.